Nanotweezers for Manipulating Untethered Micro/Nanoscale Bio‐Tools: Principles, Performance, and Highlighted Applications - Kelly Shih; Niam Zaidi; Seung Ho Lee; Huaizhi Li; Donglei Emma Fan (Advanced NanoBiomed Research)
The rapid advancement of nanotweezers for wireless manipulation of artificial micro‐ and nanoparticles has unlocked unprecedented possibilities in biomedicine. This review delves into optical, electric, and magnetic tweezers, emphasizing their roles in controlling single particles with micro/nanoscale features as miniaturized tools. Instead of providing a comprehensive review, this work highlights a select number of representative historical and contemporary examples of each type of tweezer, covering their rudimental working mechanisms, experimental setups, performance characteristics, and niche biomedical applications. Particularly, the focus lies in providing a quantitative comparison of the performances in spatial precision and degrees of freedom in controlling single particles, along with associated challenges and prospects.